2011
DOI: 10.1021/la202508q
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of n-Butanol from Dilute Aqueous Solution with Grafted Calixarenes

Abstract: INTRODUCTIONFermentation-derived butanol is a potential renewable fuel that has several advantages over other biofuels, including a higher energy density than ethanol and better solubility with current hydrocarbon fuels because of its relative nonpolarity. However, the recovery of the product from ABE fermentation broths is complicated by the low concentrations inherently yielded by the fermentation process because of the cytotoxicity of Clostridium acetobutylicum strains. 1 Because the normal boiling point of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…These results suggested that differences in the adsorption between materials were largely influence by the non-specific van der Waals interactions occurring between the n-butyl chain of the butyl group in TBT, as well as the alkyl R groups on the calixarene upper rim. This is consistent with the results found by Thompson et al [36].…”
Section: Effect Of Contact Timesupporting
confidence: 94%
See 1 more Smart Citation
“…These results suggested that differences in the adsorption between materials were largely influence by the non-specific van der Waals interactions occurring between the n-butyl chain of the butyl group in TBT, as well as the alkyl R groups on the calixarene upper rim. This is consistent with the results found by Thompson et al [36].…”
Section: Effect Of Contact Timesupporting
confidence: 94%
“…The first layer capacity was defined as the calixarene loading, while the second layer inherently represents all external adsorption sites, including those on the residual oxide surface, as well as any non-cavity sites associated with calixarenes (for example, on the outer surface of the tert-butyl groups). The latter also includes interstitial sites between adjacent grafted calixarenes [36]. A comparison of the materials MCM-TDI-C4, MCM-TDI-PC4 and MCM-TDI-C4S, in which the only difference in calixarene structure is the R group, shows that the uptake increased as the size of the hydrophobic R group changes from H to tert-butyl.…”
Section: Effect Of Contact Timementioning
confidence: 99%
“…73 To find an analogous relationship between calixarene polarity and adsorption strength, the Hammett constants were used. The computational results indicate that the cavity dehydration is the strongest driving force behind host-guest complexation in water.…”
Section: Methodsmentioning
confidence: 99%
“…73 Adsorption on these materials involved the exchange of solvent water molecules for adsorbate molecule within the calixarene cavity. For such hydrophobic calixarenes (R=H or alkyl) the adsorption is driven by weak intermolecular van der Waals forces.…”
Section: 2mentioning
confidence: 99%
“…In the proposed method, -OH groups on the surface of silica is turned into active -OSiCl 3 groups, and calixarene is attached to the surface over the nucleophilic attack of lower-rim phenolic -OH groups of calixarene [56]. As can be seen, in this methodology no spacer arm was used.…”
Section: Other Methods Of Immobilizationmentioning
confidence: 99%